2006
DOI: 10.1117/12.659463
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz NDE for metallic surface roughness evaluation

Abstract: Metallic surface roughness in a nominally smooth surface is a potential indication of material degradation or damage. When the surface is coated or covered with an opaque dielectric material, such as paint or insulation, then inspecting for surface changes becomes almost impossible. Terahertz NDE is a method capable of penetrating the coating and inspecting the metallic surface. The terahertz frequency regime is between 100 GHz and 10 THz and has a free space wavelength of 300 micrometers at 1 THz. Pulsed tera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…4 one can observe that for higher frequencies and broader opening angles the resolution improves significantly when applying SA processing. Comparing these theoretical resolutions with the ones obtained with traditional THz imaging (a resolution of 3 mm is obtained with a 0.2 THz CW system [8], using a pulsed system resolutions of 2 to 3 mm are obtained [3], [7], [9], [10]), indicates an improvement of at least a factor of 2.…”
Section: B Expected Resolutionsmentioning
confidence: 89%
See 2 more Smart Citations
“…4 one can observe that for higher frequencies and broader opening angles the resolution improves significantly when applying SA processing. Comparing these theoretical resolutions with the ones obtained with traditional THz imaging (a resolution of 3 mm is obtained with a 0.2 THz CW system [8], using a pulsed system resolutions of 2 to 3 mm are obtained [3], [7], [9], [10]), indicates an improvement of at least a factor of 2.…”
Section: B Expected Resolutionsmentioning
confidence: 89%
“…Exceptions are published results related to interferometry rather than actual synthetic aperture imaging [2], [3] or small scale SA results based on THz impulse ranging [4] on reflective and opaque objects. This paper will help to fill up this research gap in two ways: by demonstrating the extension from SA(R/S) [5], [6], towards SAT and by exploring the applications reachable combining THz waves and SA imaging in the domain of NDT [7].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This paper reported that the resolution was limited to ~ 10 μm. Another paper reported that surface roughness differences below ~ 10 μm were indistinguishable from the metallic background when searching for corrosion under paint [5].…”
Section: Paint Thickness Over Metallic Surfacesmentioning
confidence: 99%
“…Since most composite materials have a maximum transparency in the sub THz (typically between 0.1 and 0.8 THz), the minimum wavelength and thus the minimum opening angle one can use is limited and therefore the achievable azimuth resolution. A set of optics is responsible for keeping the opening angle small and the positioning and fine tuning of these optics need to be done with care [3], [4]. It should be noted that this resolution is only reached for a certain layer within the illuminated object given the so-called beam focusing depth inherent to the used optics.…”
Section: Introductionmentioning
confidence: 99%